Intervenções farmacêuticas para promoção do uso racional de medicamentos em doenças crônicas não-transmissíveis, na atenção primária à saúde - Obreli Neto, Paulo Roque (2011)
This study aims to evaluate the criteria and procedures for the selection of antidiabetic and antihypertensive drugs purchased by the public health network of the cities in the Ourinhos Micro-region, Sao Paulo, Brazil. A cross-sectional, multi-center, exploratory, quantitative study was developed in the 12 cities that constitute the Ourinhos Micro-region. The data obtained showed that cities standardize and purchase a large number and diverse range of pharmaceutical specialties, including several drugs that are not included in the 2008 National List of Essential Drugs (Rename), administrative rule No. 3237 issued on December 24, 2007 and the list of drugs of Dose Certa, a medication program by the Sao Paulo State Government. A large variation between costs of interchangeable drug was observed. In conclusion, pharmacoeconomic research in the selection process of drugs, in combination with interventions involving prescribers and Judiciary Power will reduce public spending allocated to medication purchase.